Examining the Relationship Between Body Like and Interaction Anxiety In Terms of Different Variables - Çetinkaya, Turan; Kırtepe, Abdurrahman (METİN YAMAN, 2025)
The purpose of this study is to examine the body liking and interaction anxiety levels of students studying at the faculty of sports sciences in terms of different variables and to reveal the relationships between them. 278 students studying at different departments of the faculty of sports sciences of a state university participated in the study. In the study, a personal information form was used to determine demographic variables, a “body liking scale” was used to measure participants’ body perception, and an “Interaction Anxiety Scale” was used to measure interaction anxiety. The data were tested with descriptive statistics, independent sample T-test, one-way analysis of variance ANOVA, and Pearson correlation test. As a result of the statistical analyses, it was observed that the participants’ body liking and interaction anxiety levels did not differ significantly in terms of gender and family income variables, and a significant difference was observed in body liking and interaction anxiety levels in terms of age and sports variables, respectively. According to the correlation analysis results conducted for the relationship between participants’ body liking and interaction anxiety levels, a low-level, negative, and insignificant relationship was found between the scales.

Bu araştırmanın amacı spor bilimleri fakültesindeki öğrenim gören öğrencilerin bedeni beğenme ve etkileşim kaygısı düzeylerinin farklı değişkenler açısından incelenmesi ve aradaki ilişkilerin ortaya konulmasıdır. Araştırmaya bir devlet üniversitesinin spor bilimleri fakültesinde farklı bölümlerde öğrenim gören 278 öğrenci katılmıştır. Araştırmada veri toplama aracı olarak demografik değişkenlerin belirlenmesine yönelik kişisel bilgi formu, katılımcıların beden algısını ölçmek için “bedeni beğenme ölçeği” ve etkileşim kaygılarının ölçülmesi için “Etkileşim Kaygısı Ölçeği” kullanılmıştır. Veriler betimsel istatistikler, bağımsız örneklem T-testi, tek yönlü varyans analizi ANOVA ve pearson korelasyon testi ile test edilmiştir. İstatistiksel analizler sonucunda katılımcıların cinsiyet ve aile gelir değişkenleri açısından bedeni beğenme ve etkileşim kaygısı düzeylerinin anlamlı olarak farklılaşmadığı, yaş ve spor yapma değişkenleri açısından ise sırasıyla bedeni beğenme ve etkileşim kayısı düzeylerinde anlamlı farklılık gözlenmiştir. Katılımcıların bedeni beğenme ve etkileşim kaygısı düzeylerinin ilişkisine yönelik yapılan kolerasyon analizi sonuçlarına göre ölçekler arasında düşük düzeyde, negatif ve anlamsız ilişki bulunmuştur.
Bedeni Beğenme Ve Etkileşim Kaygısı Arasındaki İlişkinin Farklı Değişkenler Açısından İncelenmesi
Keywords: Physical Training and Sports Pedagogy; Beden Eğitimi ve Spor Pedagojisi; Exercise and Sports Psychology; Egzersiz ve Spor Psikolojisi